ANALISIS SISTEM HUKUM DAN PERADILAN AGAMA DI NEGARA SOMALIA - Maulidah, Chabibatul; Asasriwarni, Asasriwarni; Zulfan, Zulfan (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
The purpose of this writing is to find out the legal system in the State of Somalia, the implementation of religious justice and the authority of religious justice in the State of Somalia. In this writing, the author uses a normative legal approach method and the results are analyzed through descriptive analysis, namely describing and explaining the legal system, the implementation of religious justice and its authority in the State of Somalia. The main data sources obtained in this study through several literature studies. With the results of research the Somali State before independence adhered to the British and Italian colonial legal systems, after independence it became a country with a multi-party parliamentary legal system. The State of Somalia has four court systems, first, the Supreme Court. Second, the Court of Appeal. Third, Regional Courts. Fourth, District Courts.